Peran Artificial Intelligence (Ai) terhadap Perkembangan Kognitif, Sosial, dan Emosional Peserta Didik: Sebuah Studi Literatur Komprehensif - El-vita Rizqi Awalia; Hanifah Setyanigrum; Amanda Aulia Nabiihah; Rara Klaucia (Universitas PGRI Madiun, 2026)
This study aims to examine the impact of AI on students' cognitive, social, and emotional development through a Systematic Literature Review (SLR). The findings reveal that AI enhances cognitive development by providing personalized learning experiences and improving conceptual understanding. However, excessive dependence on AI may reduce students' working memory and problem-solving skills due to cognitive offloading. Socially, AI supports collaborative learning but may also decrease authentic interpersonal interactions and empathy. Emotionally, while affective computing can help identify students' emotional conditions, intensive interaction with AI may encourage unhealthy emotional attachment through anthropomorphism. This study highlights the importance of implementing AI through a hybrid pedagogical approach, strengthening AI ethics literacy, and prioritizing students' psychological well-being.